Analisis Public Service Motivation Aparatur Sipil Negara Generasi Milenial dan Generasi Z di Indonesia - Balqis, Amanda; Ambardi, Defira; Siburian, Steven Manuel; Cempaka Mulia, Imas (LPPM STIA Lancang Kuning Dumai, 2025)
Public Service Motivation (PSM) plays an important role in the performance of the State Civil Apparatus (ASN) of the Millennial and Z Generations that now dominate the Indonesian bureaucracy. The characteristics of both generations that are idealistic and prioritize the meaning of work make public service motivation an intrinsic drive that is able to direct performance towards a more productive and service-oriented direction. Rigid and slow bureaucracy is the most dominant obstacle to the work motivation of Millennial and Z Generation ASNs. Through a qualitative method based on a descriptive-analytical approach, this research can describe the bureaucratic conditions faced by young ASNs and analyze the context that shapes the dynamics of each PSM dimension, namely attraction to politics and policies, commitment to public interest, compassion, and self sacrifice. This research also provides recommendations related to effective PSM management to achieve their potential for superior and responsive public performance.